Analisis Faktor yang Mempengaruhi Proses Pembelajaran Kimia di SMA Negeri 8 Mataram - Wulandari, Eka; Haris, Mukhtar; Ariani, Sunniarti (FKIP University of Mataram, 2024)
This research aims to find out what factors influence the chemistry learning process at the Senior High School of 8 Mataram. The type of research used is descriptive qualitative, with the subjects 28 students of class XI MIA 6, 26 students of XII MIA 3, and 2 chemistry teachers. Data were collected using interview techniques with a validated interview guide sheet then worked interactively and carried out continuously until complete and clear where data analysis activities include data reduction, data presentation and conclusions/verification. Data validity was carried out by triangulating sources and time. The results showed that the factors that influence the chemistry learning process are the factors of teachers, students, learning facilities and infrastructure, and the social environment of students at school. There are 2 inhibiting factors that affect the chemistry learning process, namely student factors and learning facilities and infrastructure factors. Student factors that influence the chemistry learning process are readiness, interest and intelligence/ability of students to understand during the learning process. While the learning facilities and infrastructure factor is in the availability of laboratory tools and materials that are not complete and adequate. Teacher factors and the social environment of students at school are not an inhibiting factor that affects the chemistry learning process, because teachers have worked optimally, optimally and professionally in conducting learning. While the social environment of students at school shows a harmonious relationship between students and teachers, students with other students, and students with the school environment both inside and outside the classroom with cool and comfortable school environment conditions.